IBU RUMAH TANGGA YANG BEKERJA SEBAGAI KONDEKTUR BUS (Studi Kasus : Pada Bus Massal Trans Metro Pekanbaru) - Simarmata, Raun Mochtar Harapan; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The research was conducted in Pekanbaru City with the aim to obtain information about woman working in urban specially housewives who work as bus conductor. The problems in this research are (1) How are the characteristic of housewives who work as bus condector? (2) How is the division of the domestic role and the role of the public housewife who work as bus conductor?.The title of this research is : “Housewife Who Works as Bus Condector”. The research aimed to find out the characteristics of housewife who work as bus conductor abd to know the division of domestic role and public role of housewife who work as bus conductor. In this study the subject of research amounted to six people. Subjects in thus study are housewives who work as a bus conductor , have a husband and have children. Data collection in this research is primary data obtained from research subject by observation and indepth interview and secondary data obtained from trans metro pekanbaru. after doing this research, housewife who work as bus conductor that has age ranged from 30-40 years and pursued the last education level that is one Diploma one (D1)and five others high school (SMA) equal. The role of houseviwe who work as a bus conductor becomes divided when working and when not working. Housewives can fulfill their roles such as serving the husband, taking care of the child and doing homework when the housewife is off to work as a bus conductor.Keywords : Housewife, Working, Conductor Bus, Role